CONTRIBUTION OF FOREIGN DEBT, SUKUK, AND BONDS IN INDONESIA'S ECONOMIC GROWTH - Maharani, Devi Widhia; Widyastuti, Emy (Jurnal Ekonomi dan Bisnis Airlangga, 2024)
Introduction: Indonesia's economic growth experiences unstable conditions from year to year, The study explores their impact on Indonesia's inability to overcome government spending problems by comparing three alternative sources of Indonesian state income to support economic growth, namely foreign debt, Sukuk, and bonds. Methods: The research uses a quantitative approach derived from secondary data in the form of time series data. Foreign debt has a negative effect on Indonesia's economic growth, while sukuk and bonds have a positive effect on Indonesia's economic growth. Results: The simultaneous result is 0.948, meaning that the independent variables (foreign debt, Sukuk, and bonds) have an influence and can be explained by 94.8% of Indonesia's economic growth. Meanwhile, the remaining 5.2% is explained by other variables that are not in this research. This indicates that the foreign debt sukuk and bonds variables have a big influence on Indonesia's economic growth in 2016-2023. Conclusion and suggestion: Foreign debt must be controlled properly by the state so that an economic crisis does not occur in Indonesia. Apart from that, the government must increase the issuance of sukuk and bonds to meet the needs of the deficit APBN.